2021
DOI: 10.1007/s11368-021-03081-z
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of metal-contaminated mine tailings by the application of organic and mineral amendments

Abstract: Purpose Tailings are generally characterized by severe physicochemical conditions that limit the establishment of vegetation. The present study aimed to select suitable combinations of organo-mineral amendments to improve the physicochemical, biochemical, and biological properties of spolic technosols, highly contaminated with metals. Materials and methods Several substrates were prepared by mixing mine tailings (MT) of an abandoned mining area with non-contaminated agricultural soil (anthrosol), green waste c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Bacterial enumeration and enzymatic activities showed an apparent deterioration of microbial communities in the mine tailings, since no viable bacterial cells were detected, and dehydrogenase enzyme activity was extremely low [37]. Further, [38] pointed out that microbial activity in metal-polluted bare soils is disrupted by the toxic effects on microorganisms due to the absence of vegetation cover. It is worth noting that [39] showed that microbial diversity and structure in the rhizosphere and in bulk soils from mine tailings were mainly influenced by the presence of pioneer plants and the environmental conditions, especially nutrient elements and Fe contents, alongside plant community colonisation.…”
Section: Biological Characterisation Of Iron Ore Mine Tailingsmentioning
confidence: 99%
“…Bacterial enumeration and enzymatic activities showed an apparent deterioration of microbial communities in the mine tailings, since no viable bacterial cells were detected, and dehydrogenase enzyme activity was extremely low [37]. Further, [38] pointed out that microbial activity in metal-polluted bare soils is disrupted by the toxic effects on microorganisms due to the absence of vegetation cover. It is worth noting that [39] showed that microbial diversity and structure in the rhizosphere and in bulk soils from mine tailings were mainly influenced by the presence of pioneer plants and the environmental conditions, especially nutrient elements and Fe contents, alongside plant community colonisation.…”
Section: Biological Characterisation Of Iron Ore Mine Tailingsmentioning
confidence: 99%
“…The Kettara mine tailings presented very low contents of TOC, TN, and available P, constituting major limiting factors for the establishment and development of plants in these areas [8,22,38,39]. Indeed, low levels of organic matter and nutrients are commonly found in mine tailings [40][41][42][43], which may be explained by the fact that these wastes have resulted from a succession of ore processing stages [44].…”
Section: Metal Tolerancementioning
confidence: 99%
“…Exploring these beneficial interactions is a valuable tool to improve the overall effectiveness of phytoremediation strategies in metal-contaminated areas. Several authors have reported the beneficial effects of inoculating plant growth-promoting rhizobacteria (PGPR) on plant establishment and development in metal-contaminated areas [ 6 , 8 , 23 , 25 , 26 , 27 ]. Microbial inoculants are known to decrease the availability of contaminants and enhance plant growth under stressed conditions through various mechanisms, including the production of indole-3-acetic acid (IAA) and siderophores, the solubilization of mineral phosphorus, and the activity of the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase [ 8 , 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%